EFFECT OF CULTIVARS AND PLANTING DATE ON THE FIELD EMERGENCE OF SUNFLOWER. - Hassan, Mushtaq; Hamza, Jalal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
ABSTRACT This study aimed to investigate effect of genetic and environmental factors and their interaction on field establishment of sunflower, due to the weakness and variability of emergence. A field experiment was conducted during the fall of 2023 and spring of 2024 seasons at station A, one of the research stations affiliated to the College of Agricultural Engineering Sciences, University of Baghdad. The goal was to improve field emergence rates, reduce emergence duration, and enhance chlorophyll content and photosynthesis. A split plot arrangement within Randomized Complete Block Design with four replications was used. The main factor was planting dates, and the secondary factor was three sunflower cultivars (Aqmar, Flammy, and Sakha). Results showed that the July 10 planting date had the best field emergence, while June 1 resulted in better plant height and leaf area index in the fall. Similarly, the March 30 planting date showed superior emergence rates and plant height in the spring. The Flammy cultivar consistently outperformed others in emergence and growth characteristics across both seasons. This suggests that genetic factors significantly influence emergence rates and plant performance under varying environmental conditions.